Sexualization reduces helping intentions towards female victims of intimate partner violence through mediation of moral patiency. (2nd November 2016) - Pacilli, Maria Giuseppina; Pagliaro, Stefano; Loughnan, Steve; Gramazio, Sarah; Spaccatini, Federica; Baldry, Anna Costanza
Abstract : This paper examines the influence of female sexualization on people's willingness to provide help in cases of intimate partner violence (IPV). We examined how sexualization may make women seem lacking moral patiency and moral virtue both of which may lead to a reduced willingness to help. In the first study, participants read a fictitious newspaper article describing an IPV incident. They were then presented with a picture of the ostensible victim depicting the woman with either a sexualized or non‐sexualized appearance. Participants judged both the victim's moral patiency and morality, and then expressed their willingness to provide help to that victim. Although the sexualized victim was viewed as a lesser moral patient (Studies 1 and 2) and as less moral (Study 2), it was seeing the victim as unworthy of moral patiency rather than lacking moral virtue (immoral) that linked sexualization to reduced help. Controlling for participants' sexism and women's admission of infidelity, Study 2 replicated that sexualization reduced helping intentions through a lack of moral patiency. Practical implications are discussed.